Soluble Fibrin Monomer Complexes, Plasma Fibrinolytic Activity and Aortic Wall - Wojewski, A; Samochowiec, L; Zajączkowski, T; Szyszka, K; Wojewska-Zajączkowska, E; Abucewicz, A (Thrombosis and Haemostasis, 1972)
It has been stated that in prolonged CS2 intoxication of albino rats, the percentage of soluble fibrin monomer complexes in blood increases and there is a drop in plasma fibrinolytic activity. Simultaneous serotonin administration lowers the fibrinolytic activity to still greater extent. Prolonged CS2 intoxication does not alter the antiparacoagulating activity of the aorta. Deseril and cinarine administration elevates the aortic antiparacoagulating activity, while serotonin decreases it.